Azores UNESCO Global Geopark: Where Volcanoes Tell us their Stories - Eva Lima; Salomé Meneses (Geoconservation Research)
The Azores UNESCO Global Geopark, located in the North Atlantic Ocean is a volcanic archipelago with several non-inhabited islets and nine inhabited islands. The 27 volcanic systems with polygenetic central volcanoes and volcanic ridges, most of them active but dormant, represent an exuberant geological heritage, most of which (77% of geosites) is protected. The quantity and quality of the Azorean geosites, their international relevance, and high range of geodiversity, together with the rich biodiversity and the notable cultural heritage of the archipelago sustain the Azores UNESCO Global Geopark through the motto “Nine Islands - One Geopark”. The Azores Geopark, the first archipelagic geopark in the world, is established on the basis of 121 geosites distributed across the nine islands and surrounding marine area. The unique geological and geographical setting of the archipelago allowed the development of outstanding landscapes and a culture that is deeply linked to volcanic eruptions and earthquakes. One of the priorities of the geopark is to provide the tools and knowledge for sustainable use of this heritage e through geotourism. Here, we review the Geopark, and introduce a new geosite, the Ponta da Ajuda, the largest and best outcrop of columnar jointing on São Miguel island.